INTENSITAS GUN LIGHT SEBAGAI FASILITAS KESIAGAAN DARURAT BANDARA - Agustine, Mega; Sulthon Alfikri, Ausydana; Louis Perillo, Oscar; Baskoro, Sulistiyo; Diriyanti Novalina, Susi (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
The communication failure factor is one of the factors that causes many accidents in Indonesia, especially to the aircraft. Aircraft experiencing ground-air communication failure in aviation is one of the services that must be prioritized. This study aims to determine the importance of the intensity of the use of a gun light as an emergency preparedness tool that serves to provide an instruction signal to aircraft experiencing communication failures. In this study, the author uses the calculation of the light intensity formula in physics to determine whether or not the intensity of a gun light is contained in the Sultan Mahmud Badaruddin II International Airport Tower in Palembang. If after using this calculation the intensity of the gun light does not meet the standard, the airport party can increase the intensity of the gun light and carry out routine maintenance to ensure that the light intensity does not decrease from the gun light.